Fermentasi Etanol dengan Bahan Baku Produk Sakarifikasi Singkong oleh Aspergillus niger dengan Menggunakan Isolat Saccharomyces spp. (NKB dan NKC) - Herawati, Titin; Tri Suharni, Theresia (Jurusan Biologi UIN Alauddin Makassar, 2013)
Nowdays the production of petroleum energy resource decreases in every years. Ethanol is one of renewable source of energy, it can substitution of fosil fuel. Ethanol can be produced from fermentation by Saccharomyces. The raw material of ethanol fermentation is carbohydrate rich organic. Cassava is one of efisien based material for ethanol fermentation because of its attainable price and availability. The objectives of this study were to isolation yeast from coconut neera, and use the isolate as microbial etanol fermentation from cassava. The research was started with isolating yeast from coconut neera, and then how to identified the yeast isolates by morphological and physiological characteristic. Then next process was saccharification the cassava by Aspergillus niger. Product of saccharification added by molasses to obtain 10% and 15% reducing sugar content and subjected for ethanol fermentation. The product of fermentation was analysed for the ethanol concentration by the conway microdiffuse and GCMS methode, Reducing sugar concentration was determined by DNS methode, total yeast was determined by spectroscopy methode and pH was determined by pH meter. The result showed that the isolation from coconut neera get 4 yeast isolate Saccharomyces spp. namely NKA, NKB, NKC, and NKD. The NKB and NKC isolates were choosen as candidate being used for ethanol fermentation process. The process saccharification produced 8,43% of reducing sugar. The result of ethanol fermentation process from the product saccharification of cassava and molasse mixture with content 10 % of reducing sugar were: NKB 4,19% and NKC 5,19 %. Whereas the result ethanol fermentation from the product saccharification of cassava and molasse mixture with content 15 % of reducing sugar were: NKB 6,75% and NKC 6,34 %. Based on this study, it capable concluded that mixed of the product saccharification process by cassava and molasse can be used as raw material fermentation process of ethanol by Saccharomyces spp. isolate NKB and NKC which are to isolate from coconut neera.Keywords: cassava, ethanol fermentation, molasses, saccharification, Saccharomyces spp.